Perkembangan Aplikasi Teknik Kriopreservasi untuk Konservasi dan Mendukung Program Pemuliaan Tanaman - Roostika, Ika (Jurnal AgroBiogen, 2013)
In the beginning, cryopreservationtechnique was primarily used for germplasmslong-term storage as passive collection because cell divisionand metabolism process can be stopped at super lowtemperature, commonly in liquid nitrogen. The technique issuitable for vegetative propagated plants and recalcitrantseeds. Recently, its application is extending for storing manyspecies and orthodox seeds. In this paper, the developmentof cryopreservation application is discussed. In Indonesia,cryopreservation is being studied but the application ofcryopreservation has been significantly developed abroad.The application of cryopreservation technique is not only forpreserving passive collections but also for storing activecollections, including to provide plant materials for hybridization,cellular engineering, genetic transformation, as wellas pathogens eradication or cryotherapy. It is concluded thatcryopreservation plays an important role in conventional andmodern plant breeding program.